Religious studies - Abbott, Lorraine; Clarke, Steve (Dynamic learning, 2016)
Motivate every student to deepen their understanding and fulfil their potential by following a stimulating, well-paced course through the strengthened content requirements; produced by the leading Religious Studies publisher and OCR's Publishing Partner.- Equips students with the detailed knowledge they need to succeed with clear, lively explanations that make key concepts accessible to all ability levels- Provides opportunities for students to learn, revise and develop their knowledge and skills through a variety of engaging activities, discussion points and extension tasks to